Karyotype and RAPD Analysis in Five Potato Varieties (Solanum tuberosum L.) - Alam, Riffat Ara; Habib, Md Ahashan; Alam, Sheikh Shamimul (Bangladesh Journal of Botany, 2012)
Two native and three high yielding potato varieties available in Bangladesh were studied cytogenetically at molecular level to get a preliminary idea about their genomes. These varieties possess 2n = 4x = 48 chromosomes. Each variety has definite centromeric formula. Presence of maximum metacentric chromosomes suggested their karyotypes as symmetric type. The range of individual chromosomal and total length of 2n chromosome complements was also distinct in five varieties. Heteromorphicity regarding centromeric position suggesting the occurrence of structural aberration in respective homologous pairs. Seven primer combinations were used for RAPD finger printing. A few common RAPD bands suggested the sharing of genomic fragments among five varieties. However, each variety showed specific characteristic RAPD bands. Therefore, each variety has characteristic karyotype and RAPD markers. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11088 Bangladesh J. Bot. 41(1): 105-110, 2012 (June)